STUDI KENYAMAN AKUSTIK PADA RUANG AULA BMKG STASIUN KLIMATOLOGI KELAS 1 DELI SERDANG - Zubair Aman Daulay; Abdul Halim Daulay; Widia Arti Syafitri (UIN Sumatera Utara Medan, 2023)
The purpose of this study was to determine the acoustic comfort level of the BMKG Hall Class 1 Deli Serdang Climatology Station before and after the treatment of the room in the form of adding sound-absorbing materials. The purpose of this study was to measure the noise level and optimize the effect of noise with acoustic comfort standards in accordance with KEPMENLH No. 48 of 1996 concerning Noise Level Standards in the BMKG Hall of Class 1 Deli Serdang Climatology Station. Sample Materials The materials used for sound absorption in the room are newsprint pulp and cork waste (Styrofoam) with a thickness of 3 cm. This research is motivated by the high noise below in the room which causes hearing discomfort in the room. The results of the physical test of newsprint and cork pulp (Styrofoam) at frequencies of 125 Hz, 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, and 4000 Hz obtained absorption coefficients of 0.47, 0.36, 0.48, 0.36, 0.55 and 0, 59 with the results of Reverberation Time (RT) calculations at frequencies of 125 Hz, 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, and 4000 Hz, the results obtained are RT 2.13 s, 1.35 s, 1.01 s, 0.80 s, 0.79 s, 0.82 s.